The maternal periodontal disease as a risk factor of prematurity and low birth weight - Dulanto Vargas, Julissa (2010)
The objective of the study was to evaluate the relationship between the maternal periodontal disease (EP) and the premature delivery (PP) and the low birth weight (BP). The study was a case-control study with 69 mothers, 19 cases (mothers of newborns with premature deliveries and low birth weight (PPBP)), and 50 controls (mothers of babies with gestational age > 37 weeks and birth weight > 2500g) at the “Madre Niño San Bartolomé” Teaching Hospital. The mothers were interrogated and their clinical histories reviewed. Data was recorded as follows: school level, marital status, smoking, alcohol and drug habits. Within 48 hours after birth delivery, one single examiner evaluated the modified periodontal disease index (IEP) recording the periodontal indicators: probing depth, clinical attachment level, bleeding on probing, gingival inflammation and bleeding and bacterial plaque. The statistical analysis included the frequency distribution and the Odds Ratio test. Mothers with worse bacterial plaque OR conditions: 1,45 (IC 95% 1,07 – 1,97); gingival inflammation OR: 2,14 (IC 95% 1,35 – 3,39) and clinical attachment level OR: 2,8 (IC 95% 1,55 – 5,33) were found to be related to premature delivery and low-birth-weight children. The maternal periodontal disease increases the risk of premature births and low birth weight.